Logistical challenges and design considerations for studies using acute anterior cruciate ligament injury as a potential model for early posttraumatic osteoarthritis. Issue 3 (30th June 2016) - Lattermann, Christian; Jacobs, Cale A.; Bunnell, Mary Proffitt; Jochimsen, Kate N.; Abt, John P.; Reinke, Emily K.; Gammon, Lee G.; Huebner, Janet L.; Kraus, Virginia B.; Spindler, Kurt P.
ABSTRACT: Anterior cruciate ligament (ACL) injuries are common and lead to posttraumatic osteoarthritis (PTOA) in a high percentage of patients. Research has been ineffective in identifying successful treatment options for people suffering from symptomatic PTOA resulting in a shift of focus toward the young, ACL injured patients at risk of developing PTOA. Randomized clinical trials examining the very early phase after ACL injury are ideal to study this population; however, these trials face significant challenges regarding recruitment as well as reproducibility of patient‐reported outcomes (PROs) and inflammatory and/or chondrodegenerative biomarkers associated with early PTOA. The aim of this work was to develop an approach to allow for early recruitment into an RCT for early treatment following ACL injury and to analyze the variability of commonly used measures and biomarkers at various time points after injury. This paper reports the study design and data related to the first month of treatment for the placebo group of an ongoing 2‐year clinical trial to evaluate the effect of an early intra‐articular intervention after ACL injury. The results of this study suggest that acute ACL injury results in early changes of both inflammatory and chondrodegenerative biomarkers. These results also provide vital information for researchers to consider when developing future protocols, both related to the logistics of early patient enrollment as well as the appropriate timing of biomarker and patient‐reported outcome collection. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:641–650, 2017.